Pengaruh Sistem Informasi Manajemen, Pelayanan, dan Kepemimpinan Terhadap Indeks Kepuasan Masyarakat di Kota Tangerang - Farid Bintoro Aji; Edi Abdurachman (ComTech: Computer, Mathematics and Engineering Applications, 2011)
As a public service provider the government faces a lot of problems associated with the improvement of public service quality through excellent service performance and high quality service products. Leadership factor also plays an important role in service organizations to ensure the effectiveness of the organization. Based on earlier ideas, a research is conducted towards the trade business license service delivery by local government of Tangerang which focuses on aspects of information systems management, service performance, and leadership in relation to the level of community satisfaction. There are several methods of data collection and information, such as questionnaires, interviews, field observation and literature study. The data collected were analyzed using the method of regression analysis, correlation analysis, and chi square test. The analysis showed that there is a significant relationship between the variables of the study. Therefore, it can be concluded that management information systems, service performance, and leadership has significant effects on the level of community satisfaction.